MENEMUKENALI MASYARAKAT ADAT SEBAGAI BASIS â€œKEBHINNEKATUNGGALIKAANâ€ MENUJU INTEGRASI BANGSA - Djaja Hendra (Jurnal Ilmiah Mimbar Demokrasi, 2014)
Put the indigenous peoples to be followed by the term "all still alive and in accordance with the development of society" or other terms that convey the same in the constellation of state regulations, no doubt point to the existence of ideological claims unilateral and provocative. On the one hand, indigenous peoples as being faraway, while we are on the other side so arrogant and intervention while differentiating themselves into, "so another". Disorder was demonstrated through planned regulatory policies, structural and massive for our indigenous people buried in the frame word 'all still alive' and so on. Though there are many other socio-cultural based that sustains the existence and survival on indigenous peoples outside of agriculture. The Kebhinnekatunggalikaan was eminent merely ended motto compliance rigid beliefs and unilateral. If so integration with the nation as the adhesive is based on the awareness of the need for unity in fact not be as, a mere mirage.